1999
DOI: 10.1109/52.776956
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing user requirements by use cases: a goal-driven approach

Abstract: B ecause there is no systematic way in existing use-case approaches to handle nonfunctional requirements, the authors propose an approach to analyze and evaluate use cases with goals and to structure use-case models. se-case approaches are increasingly attracting attention in requirements engineering because the user-centered concept is valuable in eliciting, analyzing, and documenting requirements. 1-5 One of the main goals of the requirements engineering process is to get agreement on the views of the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Consequently, it is important to specify not only how system objects interact to achieve the goal of each base use case, but also how these objects interact to implement the crosscutting concerns of each aspectual use case as well as where the effects take places with respect to the aspectual use case's corresponding base use cases. As a continuation of our previous research, [8][9][10]24 we augment the use case speciÞcation with aspectual property to document the responsibility of an aspectual use case. Through the speciÞcation of aspectual property, aspectual behavior can be modeled within the proposed aspectual sequence diagrams together with three types of aspectual interaction operators to perform on the base use cases.…”
Section: Aspectual Behaviors Modelingmentioning
confidence: 99%
“…Consequently, it is important to specify not only how system objects interact to achieve the goal of each base use case, but also how these objects interact to implement the crosscutting concerns of each aspectual use case as well as where the effects take places with respect to the aspectual use case's corresponding base use cases. As a continuation of our previous research, [8][9][10]24 we augment the use case speciÞcation with aspectual property to document the responsibility of an aspectual use case. Through the speciÞcation of aspectual property, aspectual behavior can be modeled within the proposed aspectual sequence diagrams together with three types of aspectual interaction operators to perform on the base use cases.…”
Section: Aspectual Behaviors Modelingmentioning
confidence: 99%
“…At requirement Engineering phase several Goal Oriented Approaches to handle NFR have been suggested such as i*, framework and GRL (Goal -Oriented Requirement Language), SIG (Soft goal interdependence graph) [21,25,35,34]. All these goal oriented approaches are based on identifying NFR as soft goal which needs to be satisfied (within an acceptable limit, or goals merely met) or "not satisfied" at all.…”
Section: Section 3: Literature Survey: Current Methods To Handle Nfr mentioning
confidence: 99%
“…Reviewing the literature, we found that several studies [6]- [9] applied different approaches to identify cooperative, conflicting, and irrelevant relationships among software requirements.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Lee and Xue [9] used a goal based approach to explore cooperative, conflicting, and irrelevant relationships between user requirements. They represented the user requirements by building the use case models with the associated goals.…”
Section: Background and Related Workmentioning
confidence: 99%